Proactive Inhibitory Control of Response as the Default State of Executive Control - Criaud, Marion; Wardak, Claire; Ben Hamed, Suliann; Ballanger, Benedicte; Boulinguez, Philippe (Frontiers in Psychology, 2012)
Refraining from reacting does not only involve reactive inhibitory mechanisms. It was recently found that inhibitory control also relies strongly on proactive mechanisms. However, since most available studies have focused on reactive stopping, little is known about how proactive inhibition of response is implemented. Two behavioral experiments were conducted to identify the temporal dynamics of this executive function. They manipulated respectively the time during which inhibitory control must be sustained until a stimulus occurs, and the time limit allowed to set up inhibition before a stimulus occurs. The results show that inhibitory control is not set up after but before instruction, and is sustained across time. Consistent with our previous neuroimaging findings, these results suggest that proactive inhibition of response is the default mode of executive control. This implies that top-down control of sensorimotor reactivity would consist of a temporary release (up to several seconds), when appropriate, of the default locking state, rather than an active long-lasting inhibitory control in unpredictable environments. This conclusion is discussed with regard to current anatomo-functional models of inhibitory control and to methodological features of studies of attention and sensorimotor control.